Deformation behaviour of concrete with different moisture contents subjected to compressive creep and cyclic loading - Kern, Bianca; Podhajecky, Anna-Lena; Lohaus, Ludger; Haist, Michael; Oneschkow, Nadja (Materials and structures, 2024)
The expected long-term deformations of concrete structures are calculated using creep models, derived from experiments performed with constant mechanical loads. However, in the majority of real structures, such as bridges, constant creep loads are superimposed with cyclic loads of substantial magnitude. Additionally, such structures are subject to changes in environmental conditions (temperature and humidity). Deformation measurements of existing bridges have shown significant underestimations by established creep models, which might be traced back to the superimposition of cyclic loads and different moisture contents. Therefore, the developments of strains, viscoplastic strains and modulus of elasticity under creep and cyclic loading of a normal strength concrete have been comparatively investigated for two different pore moisture contents (approx. 100 and 75%). The results show that viscous strains due to cyclic loading are significantly higher than those due to creep loading at the mean stress level of cyclic loading. Furthermore, the strains are higher for the higher moisture content. The differences in the development of the modulus of elasticity and viscoplastic strains of both load types give clear indication for load type dependent microstructural deformation mechanisms. The results obtained concerning the influence of the load type and the moisture content need to be considered for the improvement of existing models.